Performance Evaluation of Novel Piezoelectric Cantilever Beam Structure for Energy Harvesting - Tyagi, Naveen; Gaur, Anshu Mli; Mahajan, Aparna N. (Trends in Sciences, 2022)
This study proposes an elastic compact Piezoelectric energy harvester (PEH) in multiple configurations, including a single cantilever beam, a single cantilever beam with a hole, two cantilever beams with a hole contributing towards a wider operating bandwidth. The cantilever beams are designed in multiple structural forms and section shapes, including symmetrical uniform section rectangle frames. Natural frequencies, vibration modes, and output voltages of PEH are estimated using Finite element software, with the frame acting as a rigid body and the cantilever plate acting as a deformed structure. A PEH with a rectangular cantilever plate surrounded by a rigid frame is designed and attached to the vibration platform with a customized fixture in the simulation software. The design meets the requirements of natural frequency and high output voltage in the low-frequency band. The PEH structure is simulated using a variety of piezoelectric materials, primarily PZT4 and PZT5H, barium titanate, lithium niobate, zinc oxide, and polyvinylidene difluoride (PVDF) using the finite element method. In the structural configuration of two cantilever beams with holes, PEH exhibited the maximum output voltage of 32.832 V for Zinc oxide compared to other materials. So, it can be concluded that insertion of hole and variation in the geometry of cantilever structure along with frame plays a vital role in achieving a large voltage from the vibrations in PEH. HIGHLIGHTS The finite element approach was used to develop and simulate the cantilever-based piezoelectric energy harvesting structure Multiple elastic compact Piezoelectric energy harvester (PEH) designs, including a single cantilever plate, a single cantilever plate with a hole, and two cantilever plates with a hole, are simulated using different materials The frame, hole insertion, and geometry modification of the cantilever structure all play important roles in generating a substantial voltage from the vibrations in PEH This study presents an Eigen frequency analysis of different PEH structures GRAPHICAL ABSTRACT